Reformulasi hukum mengenai sanksi bagi muzakki pada uu no. 23 tahun 2011 - chumairo1, chumairo30_ (Maliki Interdisciplinary Journal, 2025)
Law Number 23 of 2011 concerning Zakat Management serves as a crucial regulation in the governance of national zakat. However, the provisions regarding sanctions for muzakki (zakat obligors) who fail to fulfill their zakat obligations are still administrative in nature and lack a deterrent effect. This has led to low compliance among muzakki in distributing zakat through official institutions and has hindered the optimal utilization of zakat as a fiscal instrument to support development and poverty alleviation. This study aims to examine the weaknesses of the sanction provisions in Law No. 23 of 2011 and formulate alternative legal reformulations that are more effective and aligned with the principles of Islamic economic law. Using a normative approach and juridical-comparative analysis, this research finds the need to strengthen the sanction aspect by integrating moral, social, and positive legal approaches. Such reformulation is expected to improve muzakki compliance, enhance the legitimacy of zakat institutions, and position zakat as a strategic instrument in the national economic system.